A study of CO2 gasification of solid carbonaceous wastes for CO2 mitigation and chemical production - PARVEZ, Ashak Mahmud (2017)
This study focuses on the utilization of solid carbonaceous wastes, the mitigation of CO2 and the development of CO2-based chemical production process which is divided into three main parts. The first part consists of the investigation of solid carbonaceous samples behaviours under pyrolysis and combustion processes. The second part covers experimental study of CO2 gasification aiming at the identification of interactions during co-gasification. Here, the presence of interactions will be further discussed, particularly in terms of increasing the gasification rate of low reactive carbonaceous sample and the effect of pyrolysis heating methods on gasification reactivity. The last part considers the thermodynamic assessment of conventional and CO2-enhanced biomass gasification. The objective is to identify the influence of CO2 as a gasifying agent in biomass gasification. Moreover, the comparisons study of bio-DME production based on conventional and CO2-enhanced gasification was also carried out in this thesis. (i) Pyrolysis of NMPCBS and combustion of solid carbonaceous materials This part consists of investigation of solid carbonaceous samples behaviours under pyrolysis and combustion processes. The objective is to explore the feasibility of the utilization of non-metallic part of waste printed circuit boards (NMPCB), including the thermal behaviours of NMPCB and its blends with two types of coals by using a thermogravimetric analyser (TGA). For individual sample, the results showed that the NMPCB had the fastest rate of pyrolysis and the highest maximum weight loss rate compared with coals, thus, the highest reactivity. These were attributed to the thermal degradation properties of the constituent elements in NMPCB. Meanwhile, based on kinetic study, it is evident that the lower heating rates favoured the pyrolysis process. For blends, it was revealed that there was 6%-7% deviation in terms of the yield of solid residue between experimental and calculated values, indicating a significant gap between the overall activation energy (Ea) of the blends and its average (Eave). Thus, it confirmed the existence of interactions in co-pyrolysis. Moreover, the combustion characteristics of an Australian coal, a suite of solid carbonaceous materials, and their blends were also investigated. A drop in both ignition temperature and burnout temperature was observed when carbonaceous wastes were blended with coal at different proportions (10 wt% and 30 wt%) which justified that there were strong interactions during the co-processing of coal with carbonaceous materials. The ignition index values of coal/polystyrene and coal/oat straw blends increased by 78% and 52%, respectively, when the blending ratio increased from 10 wt% to 30 wt%. Similarly, 2.6 times increase in combustion index was also observed in coal/oat straw blend. The presence of interactions in blends was further measured by using the root mean square interaction index (RMSII) which showed that coal/oat straw and coal/polystyrene blends had the highest RMSII values. This indicated the presence of strong interactions during co-combustion. (ii) CO2 gasification of solid carbonaceous materials The second part covers the feasibility evaluation of using CO2 as a gasifying agent, namely CO2 gasification, for various solid carbonaceous materials. The work includes the conversion of carbonaceous materials to syngas, gasification characteristics of coal, a set of waste carbonaceous materials, and their blends. The experiments were run by using a thermogravimetric analyser (TGA). The results showed that CO2 gasification of polystyrene completed at 470 °C, which was lower than those of other carbonaceous materials. This behaviour was attributed to the high volatile content coupled with its unique thermal degradation properties. Further results demonstrated that CO2 co-gasification process was enhanced as a direct consequence of interactions between coal and carbonaceous materials in the blends. The intensity and temperature of occurrence of these interactions were influenced by the chemical properties and composition of the carbonaceous materials in the blends. The strongest interactions were observed in coal/polystyrene blend at the devolatilisation stage, as indicated by the highest value of RMSII, whereas at char gasification stage, the highest interactions were found in coal/oat straw blend. The catalytic effect of alkali metals and other minerals in oat straw, such as CaO, K2O, and Fe2O3, contributed to these strong interactions, thus, the addition of polystyrene and oat straw enhanced the overall CO2 gasification of coal. On the other hand, interactions between petroleum coke and solid carbonaceous materials were also analysed with the aim of enhancing the gasification reactivity of highly unreactive petroleum coke. To achieve this, an Australian coal and gum wood were chosen for co-processing with petroleum coke. The addition of gum wood was found as the significant contributor of the enhanced gasification reactivity of petroleum coke. This is due to the combined influence of a number of unique features of bio-char, such as high surface area, more active sites, low crystalline index and the catalytic effect of alkali and alkaline earth metals (AAEM) compounds. These results confirmed that proper selection of solid carbonaceous materials for gasification of petroleum coke is an effective means to improve the conversion efficiency of petroleum coke, i.e., higher reactivity, and therefore expand its large scale utilization. In addition to coal and petroleum coke, the isothermal and non-isothermal CO2 gasification of an algal biomass (Chlorella) char were also carried out by using TGA under two different heating systems, i.e. conventional and microwave-assisted pyrolysis. Based on reactivity index, maximum peak temperature and maximum mass loss rate parameters, it was shown that microwave char had higher gasification reactivity than that of conventional char. Likewise, the activation energy value of microwave char also confirmed its higher reactivity which was found to be about 9.6% lower than that of conventional char. In addition, the physical properties of these chars, such as Brunauer-Emmett-Teller surface area, carbon crystalline structure and number of active sites, were systematically tested. Based on these properties, microwave char was found to be more reactive as demonstrated by its large BET surface area, low crystalline index and high active sites. Meanwhile, co-gasification experiments under isothermal condition revealed the existence of greater synergistic effects in coal char/microwave algae char blend than that present in coal char/conventional algae char blend. (iii) Process modelling and simulation The last part considers the process simulation of thermodynamic assessment for CO2-enhanced biomass gasification. The primary objective is to identify the influence of CO2 as a gasifying agent in biomass gasification. In this part, steam and CO2-enhanced gasification of rice straw was simulated using Aspen Plus simulator and compared in terms of energy, exergy and environmental impacts. It was found that the addition of CO2 had less impact on syngas yield than gasification temperature; the cold gas efficiency (CGE) increased with CO2/Biomass ratio. At lower ratios (below 0.25), gasification system efficiency (GSE) was below 22.1%, which is lower than that of conventional gasification. However, when CO2/Biomass ratio was increased, the GSE continued to increase and reached a peak of 58.8% at ratio of 0.87. In terms of syngas exergy, the value generally increases with CO2 addition mainly due to the increase in physical exergy. In this work, chemical exergy was found to be 2.05 to 4.85 times higher than physical exergy. The maximum exergy efficiency occurred within the temperature range of 800 oC to 900 oC, related to the peak of syngas exergy. For CO2-enhanced gasification, exergy efficiency was found to be more sensitive to temperature than CO2/Biomass ratios. In addition, the preliminary environmental analysis showed that CO2-enhanced gasification resulted in significant environmental benefits compared with stream gasification. However improved assessment methodologies are needed to better evaluate the advantages of CO2 utilization. Afterwards, process simulation of a single-step synthesis of DME based on CO2-enhanced gasification of rice straw was conducted using Aspen Plus, consisting of gasification unit, heat recovery unit, gas purification unit, single-step DME synthesis, and DME separation unit. In the simulation, highly pure DME was produced by the control of CO2 concentration in syngas to a very low level prior to synthesis. A gasification system efficiency of 36.7% and CO2 emission of 1.31 kg/kg of DME were achieved. Bio-DME production based on CO2-enhanced gasification of biomass was found to be more cost-effective as it required 19.6% less biomass than that of DME production based on conventional biomass gasification. Ultimately, the feasibility assessment of using CO2 as a gasifying agent en route to DME synthesis, exergetic and environmental evaluation of the proposed system was performed and compared with the conventional system. Based on the three performance indexes, i.e. fuel energy efficiency, plant energy efficiency and plant exergetic efficiency, the CO2-enhanced system showed a better overall performance than the conventional one. It was found that CO2-enhanced system produced 0.59 kg DME per kg gum wood with a plant energy efficiency of 65%. These two values were 28% and 5% higher than those achieved in the conventional system, respectively, which were mostly attributed to the higher DME production rate and energy output in the CO2-enhanced system. In comparison to the conventional system, the overall exergetic efficiency of the CO2-enhanced system was also higher by 7%. The evaluation on exergetic analysis of each process unit in both routes revealed that the largest loss was attributed to the gasifier unit. However, the use of CO2 as gasifying agent decreased the loss of gasifier by 15%, indicating another advantage of the proposed system. Based on the life cycle assessment (LCA) analysis of both processes, it was found that the CO2-enhanced system offered less environmental impacts compared with the conventional system. This suggests that the utilisation of CO2 as gasifying agent was the key to the more environmental friendly bio-DME synthesis system. Thus, the production of bio-DME based on CO2-enhanced gasification is of a great potential for the development of sustainable fuels.